ANALISIS PRAKTIK PEMELIHARAAN GIGI DAN MULUT BALITA SEBAGAI PENCEGAHAN EARLY CHILDHOOD CARIES OLEH ORANGTUA/WALI DI PROVINSI JAWA TENGAH - Arida Bitanajsha Zuqriefa; Bagoes Widjanarko; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2022)
Early Childhood Caries is a serious dental and oral health disease that occurs when  child is at preschool stage, where at this time, children expepriencing growth of the primary teeth, that are still    susceptible. Untreated dental caries problem on children, can cause several problems, such as being underweight, poor performance at school, school absent, and also poor quality of life. Based on the 2018 RISKESDAS, 42,11% children aged 3-4 years in Central Java is having oral health problem, but only 3.95% that receive medical care from health professional. Good oral hygine is important for oral health, and also overall health. The aim of this study is to see factors that related to oral hygiene practice for children under five years old by parents or guardians, as an effort to prevent Early Childhood Caries (ECC) in Central Java.This study is a quantitative research, with  cross sectional approach. The number of responden in this this study were 98, that determined uising purposive sampling technique. The study results showed that 51% of parents/guardians had a poor  practices at maintaining children’s oral health. Factors that influence their practice were parent’s attitude (p=0,005), parents knowledge (p=0,000), and also the accessibility of oral health information (p=0,009).